2022
DOI: 10.1101/2022.12.06.519281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coupled carbon and nitrogen cycling regulates the cnidarian-algal symbiosis

Abstract: Efficient nutrient recycling underpins the ecological success of the cnidarian-algal symbiosis in oligotrophic waters that forms the basis of coral reef ecosystems. In a stable symbiosis, nitrogen limitation restricts the growth of algal endosymbionts and stimulates their release of photosynthates to the cnidarian animal host. However, the detailed mechanisms controlling nitrogen availability in hospite and their role in symbiosis regulation remain poorly understood. Here, we studied the metabolic regulation o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The importance of diet over symbiosis appears to persist during primary polyp growth and development and into early asexual reproduction. However, in adult polyps the nutritional balance shifts towards the primacy of the symbiosis 19,20 , including our observation of a striking reliance on symbiosis for Aiptasia sexual reproduction. This has been observed in the Hydra/Chlorella symbiosis 21 , and although some aposymbiontic corals can spawn 22 , the breakdown of symbiosis likewise rather severely affects sexual reproductive success in corals (e.g.…”
Section: Role Of Symbiosismentioning
confidence: 62%
“…The importance of diet over symbiosis appears to persist during primary polyp growth and development and into early asexual reproduction. However, in adult polyps the nutritional balance shifts towards the primacy of the symbiosis 19,20 , including our observation of a striking reliance on symbiosis for Aiptasia sexual reproduction. This has been observed in the Hydra/Chlorella symbiosis 21 , and although some aposymbiontic corals can spawn 22 , the breakdown of symbiosis likewise rather severely affects sexual reproductive success in corals (e.g.…”
Section: Role Of Symbiosismentioning
confidence: 62%
“…For example, it was recently reported that endosymbionts under optimal light conditions for photosynthesis make more carbon available and stimulate nitrogen assimilation in the host. This in turn, limits nitrogen available to algal endosymbionts resulting in low densities within the holobiont [25]. In fact, it has been demonstrated that cnidarian hosts use a carbon-negative feedback loop to control symbiont proliferation [26] where supplementing additional carbohydrates significantly reduced the symbiont density through limiting their nitrogen availability.…”
Section: Discussionmentioning
confidence: 99%
“…Since its formal proposal as a model system to study cnidarian symbiosis in 2008 (Weis et al, 2008). Aiptasia has been adopted by a growing number of laboratories to explore research questions on: development and cellular regeneration (Fransolet et al, 2012;Fransolet et al, 2013;Bucher et al, the onset, maintenance, and disruption of symbiosis (Bieri et al, 2016;Bucher et al, 2016;Wolfowicz et al, 2016;Tivey et al, 2022;Rädecker et al, 2023); and metabolic interactions (Rädecker et al, 2018) among others. To date, this community of researchers has made available a genome (Baumgarten et al, 2015), developed omics tools (Lehnert et al, 2014;Baumgarten et al, 2018;Matthews et al, 2018;Simona et al, 2019;Sproles et al, 2019), closed the life cycle (Maegele et al, 2023), and openly shared their research protocols through initiatives such as the "Aiptasia Symbiosis Resource" portal (aiptasia-resource.org).…”
Section: Editorial On the Research Topicmentioning
confidence: 99%